Effect of leaching residual methyl methacrylate concentrations on in vitro cytotoxicity of heat polymerized denture base acrylic resin processed with different polymerization cycles - Canan Bural; Esin AktaŞ Günnur Deniz; Yeşim Ünlüçerçi; Gülsen Bayraktar (University of São Paulo, 2011)
OBJECTIVES: Residual methyl methacrylate (MMA) may leach from the acrylic resin denture bases and have adverse effects on the oral mucosa. This in vitro study evaluated and correlated the effect of the leaching residual MMA concentrations ([MMA]r) on in vitro cytotoxicity of L-929 fibroblasts. MATERIAL AND METHODS: A total of 144 heat-polymerized acrylic resin specimens were fabricated using 4 different polymerization cycles: (1) at 74ºC for 9 h, (2) at 74ºC for 9 h and terminal boiling (at 100ºC) for 30 min, (3) at 74ºC for 9 h and terminal boiling for 3 h, (4) at 74ºC for 30 min and terminal boiling for 30 min. Specimens were eluted in a complete cell culture medium at 37ºC for 1, 2, 5 and 7 days. [MMA]r in eluates was measured using high-performance liquid chromatography. In vitro cytotoxicity of eluates on L-929 fibroblasts was evaluated by means of cell proliferation using a tetrazolium salt XTT (sodium 3´-[1-phenyl-aminocarbonyl)-3,4-tetrazolium]bis(4-methoxy-6-nitro)benzenesulphonic acid) assay. Differences in [MMA]r of eluates and cell proliferation values between polymerization cycles were statistically analyzed by Kruskal-Wallis, Friedman and Dunn's multiple comparison tests. The correlation between [MMA]r of eluates and cell proliferation was analyzed by Pearson's correlation test (p<0.05). RESULTS: [MMA]r was significantly (p<0.001) higher in eluates of specimens polymerized with cycle without terminal boiling after elution of 1 and 2 days. Cell proliferation values for all cycles were significantly (p<0.01) lower in eluates of 1 day than those of 2 days. The correlation between [MMA]r and cell proliferation values was negative after all elution periods, showing significance (p<0.05) for elution of 1 and 2 days. MMA continued to leach from acrylic resin throughout 7 days and leaching concentrations markedly reduced after elution of 1 and 2 days. CONCLUSION: Due to reduction of leaching residual MMA concentrations, use of terminal boiling in the polymerization process for at least 30 min and water storage of the heat-polymerized denture bases for at least 1 to 2 days before denture delivery is clinically recommended for minimizing the residual MMA and possible cytotoxic effects.